The economic impact of tourism industry on economic growth in selected ASEAN countries / Siti Masayu Mohd Sharif - Mohd Sharif, Siti Masayu (2015)
This paper is made to find out the economic impact of tourism industry in selected ASEAN countries. Specifically, it is made to find out the extent of impact of certain variables on Malaysia, Thailand and Singapore‟s GDP. The data is obtained from Euromonitor and the scope of this study comprises of 3 countries randomly selected over 20 years of period dating from 1993 until 2013, thus the implementation of panel data analysis. The dependent variable is GDP and the independent variables are tourist arrival (TARR), tourism receipts (TREC), export (XPT) and FDI. Normality test, unit root test, regression analysis, correlation analysis, multicollinearity, serial correlation and heteroscedasticity were conducted to get the best regression model. From the best regression model, tourism receipts and export have positive and significant impact on the GDP of Malaysia, Singapore and Thailand. This research may help industry players and policy maker in their respective responsibility.